2020
DOI: 10.1038/s41598-020-62805-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal beta-amyloid peptides(1-40) and (1-42) in severe preeclampsia and HELLP syndrome – a pilot study

Abstract: During pregnancy, substantial alterations in cerebral plasticity, vascular remodeling and neuronal growth occur in the maternal brain. We investigated whether concentrations of selected neurodiagnostic biomarkers in the cerebrospinal fluid of women with preeclampsia/HELLP syndrome differ from those in healthy controls using enzyme-linked immunosorbent assay technique. We found that tau protein concentrations (p = 0.016) and phospho-tau/tau ratio (p < 0.001) in cerebrospinal fluid were significantly lower in 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…It is, however, possible that other mechanisms, potentially related to CSF dynamics, might play a role as well, but then all markers would move in the same direction, which was not the case in our study. In any case, our findings are in line with other publications reporting decreased CSF concentrations of tau in preeclampsia and in placental insufficiency [ 33 , 34 ]. These findings need to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…It is, however, possible that other mechanisms, potentially related to CSF dynamics, might play a role as well, but then all markers would move in the same direction, which was not the case in our study. In any case, our findings are in line with other publications reporting decreased CSF concentrations of tau in preeclampsia and in placental insufficiency [ 33 , 34 ]. These findings need to be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…Aside from its well-established role in neuronal cells, MAP-Tau contributes to the pathophysiology of placenta; it is upregulated in normal pregnancies and lowered in pre-eclampsia ( Bergman et al., 2018 ; Lederer et al., 2020 ). As viruses disrupt host immunity by converting MAP-Tau to pTau, placental function is likely altered.…”
Section: Cell-cell Fusion and Tau Hyperphosphorylationmentioning
confidence: 99%
“…The question then arises whether a pathologic production or clearance defect of beta-amyloid peptides during pregnancy could be responsible for pregnancy-related central nervous system pathologies such as eclampsia, a severe complication of preeclampsia in which pregnant women suffer seizures (Duley 2009 ). In our previous work, beta-amyloid peptide levels in CSF were found to be lower in severe preeclampsia (Lederer et al 2020 ). In a postmortem study, a lower beta-amyloid load in CSF of patients with Alzheimer’s disease correlated with increased beta-amyloid aggregates in brain parenchyma (Blennow and Zetterberg 2018 ).…”
Section: Discussionmentioning
confidence: 75%
“…Beta-amyloid peptides are products of normal cell metabolism (Canobbio et al 2015 ) and have trophic properties: for example, they capture redox metal ions and thus dampen oxidative stress (Atwood et al 2003 ). In a recent study (Lederer et al 2020 ), we reported that beta-amyloid peptides correlate with placental dysfunction.…”
Section: Introductionmentioning
confidence: 80%